2015
DOI: 10.1103/physreve.92.022714
|View full text |Cite
|
Sign up to set email alerts
|

Metapopulation dynamics in a complex ecological landscape

Abstract: We propose a general model to study the interplay between spatial dispersal and environment spatiotemporal fluctuations in metapopulation dynamics. An ecological landscape of favorable patches is generated like a Lévy dust, which allows to build a range of patterns, from dispersed to clustered ones. Locally, the dynamics is driven by a canonical model for the evolution of the population density, consisting of a logistic expression plus multiplicative noises. Spatial coupling is introduced by means of two sprea… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
13
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 31 publications
4
13
0
Order By: Relevance
“…Analytically, these results can be extracted from approximative expressions based on the theory of first-passage times [1][2][3]7]. For the cases in which φ is described by a Gaussian noise, standard first-passage times techniques find expressions for the mean lifetime which are able to reproduce the form τ ∼ e φ ∼ e K used in the application section [2,8]. However, it has been shown that the use of more sophisticated techniques can improve the preci-sion in cases in which the Fokker-plank approach fails, for instance, when assuming strong and correlated environment fluctuations [2,9,10].…”
Section: A Effective Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…Analytically, these results can be extracted from approximative expressions based on the theory of first-passage times [1][2][3]7]. For the cases in which φ is described by a Gaussian noise, standard first-passage times techniques find expressions for the mean lifetime which are able to reproduce the form τ ∼ e φ ∼ e K used in the application section [2,8]. However, it has been shown that the use of more sophisticated techniques can improve the preci-sion in cases in which the Fokker-plank approach fails, for instance, when assuming strong and correlated environment fluctuations [2,9,10].…”
Section: A Effective Modelmentioning
confidence: 99%
“…In this section we solve numerically the spatial explicit model given by Eq. (1.1) assuming a random landscape (randomly distributed patches under periodic boundary conditions) and γ(r) = e −r [8].…”
Section: B Spatial Explicit Modelmentioning
confidence: 99%
“…Moreover, the ecological factors change in time with a characteristic periodicity (seasonality) accompanied by random fluctuations. Then, the environment critical conditions for population survival rely on a combination of the spatial and temporal variability of the environment [7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the ecological factors change in time with a characteristic periodicity (seasonality) accompanied by random fluctuations. Then, the environment critical conditions for population survival rely on a combination of the spatial and temporal variability of the environment [22,35,36,[104][105][106]. Its time variability can have di erent origins.…”
Section: Habitat Temporal Behaviormentioning
confidence: 99%
“…Here, we address related fundamental questions in metapopulation theory proposing a model that includes a general dispersion process, incorporating random and selective dispersal strategies. Additionally, we investigate the model dynamics on top of a complex ecological landscape whose spatial structure can be tuned, ranging from spread to aggregated patches [36].…”
Section: Metapopulation Dynamicsmentioning
confidence: 99%